1993
DOI: 10.1152/ajpregu.1993.265.1.r261
|View full text |Cite
|
Sign up to set email alerts
|

The circadian melatonin and cortisol secretion pattern in permanent night shift workers

Abstract: In permanent night shift workers the impact of environmental time cues on the circadian system is conflicting. Rhythm adjustments to the nocturnal work schedule have been described, and their significance for tolerance to shift work is under discussion. Reports concerning the effect of this work situation on the setting of the endogenous clock are, however, inconsistent. We examined nine healthy young male permanent shift workers with high work satisfaction at the end of a week on night work and seven male con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 0 publications
4
56
1
2
Order By: Relevance
“…The findings of Roden et al (1993) are opposed to others who found wide variations in melatonin profiles, particularly the onset of melatonin release, among permanent night shiftworkers when compared to day workers (Weibel, Spiegel, Gronfier, Follenius, & Branden-Berger, 1997). Others have found forward shifts in the mean peak of melatonin as well as a lack of an identifiable acrophase during night work among permanent night shiftworkers (Quera-Salva, Defiance, Claustrat, DeLattre, & Guilleminault, 1996).…”
Section: A Laboratory Comparison Of Clockwise and Counter-clockwise Rcontrasting
confidence: 72%
See 1 more Smart Citation
“…The findings of Roden et al (1993) are opposed to others who found wide variations in melatonin profiles, particularly the onset of melatonin release, among permanent night shiftworkers when compared to day workers (Weibel, Spiegel, Gronfier, Follenius, & Branden-Berger, 1997). Others have found forward shifts in the mean peak of melatonin as well as a lack of an identifiable acrophase during night work among permanent night shiftworkers (Quera-Salva, Defiance, Claustrat, DeLattre, & Guilleminault, 1996).…”
Section: A Laboratory Comparison Of Clockwise and Counter-clockwise Rcontrasting
confidence: 72%
“…Produced by the pineal gland following its synthesis from tryptophan, concentrations of melatonin are relatively high at night and at their lowest levels during the day with the rhythm entrained by photic stimuli, exercise, certain drugs, and exogenous melatonin (Guyton & Hall, 2000). Roden, Koller, Pirich, Vierhapper, and Waldhauser (1993) examined the circadian melatonin profile for permanent night shiftworkers, compared with matched controls. The night shiftworkers as a group displayed no adaptation of circadian profiles for either melatonin or cortisol.…”
Section: A Laboratory Comparison Of Clockwise and Counter-clockwise Rmentioning
confidence: 99%
“…One issue would be to find a better variable measuring the circadian phase. Shift work is not a valid proxy since previous studies have shown that shift workers do not always have a phase shift of the circadian rhythm (8,9). Another problem to investigate would be whether the body is more sensitive or vulnerable as a result of shift work at certain ages.…”
Section: The Mortality Of Shift Workersmentioning
confidence: 99%
“…The endogenous circadian timing system, including the suprachiasmatic nucleus (SCN) in the hypothalamus and peripheral oscillators in vital organs, optimally regulates much of our physiology and behavior across the 24-h day when it is properly aligned with the sleep/wake cycle. However, shift work is generally associated with chronic misalignment between the endogenous circadian timing system and the behavioral cycles, including sleep/wake and fasting/ feeding cycles (7,8). Shift workers often experience symptoms akin to jet lag, with gastrointestinal complaints, fatigue, and sleepiness during the scheduled wake periods, and poor sleep during the daytime sleep attempts (9).…”
mentioning
confidence: 99%